THE INFLUENCE OF ONLINE, FINANCIAL MANAGEMENT, AND APPLICATION TOWARDS SALES EFFECTIVENESS: CASE STUDY ON MSMES IN BANDUNG CITY - Arismutia, Salza Adzri; Merliana, Vina (Journal of Accounting Inaba, 2022)
This study aims to analyze the effect of online financial management applications on sales of MSMEs (Micro, Small, and Medium Enterprises) in Bandung. The sample in this study used 80 MSMEs with various types of businesses including those engaged in fashion, culinary, services, and trade. This research method is quantitative with a descriptive verification approach. Data processing using SPSS application version 25 with multiple linear regression testing. The results showed that the variables had an effect on sales effectiveness. Partially, application variables have no effect on sales effectiveness, while financial management variables and online variables affect the effectiveness of MSMEs sales in Bandung City.